1999
DOI: 10.1007/s002800050974
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cisplatin cytotoxicity by terbium in cisplatin-resistant MDA/CH human breast cancer cells

Abstract: Our results suggest that the enhancement of cisplatin cytotoxicity by Tb3- is more effective in cisplatin-resistant MDA/CH cells than in cisplatin-sensitive MDA cells. Therefore, terbium is potentially useful in cisplatin combination therapy for breast cancer patients, especially for those patients who have developed resistance to the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…3A). This concentration (100 µM) is approximately double that of reported cisplatin IC 50 values in some cancer cell lines [4243] and equivalent to or below IC 50 values in some cisplatin resistant cell lines, e.g., A2780/C30, MDA/CH [4244]. Therefore, our tissue culture assay found statistically significant ROS release at cisplatin concentrations encountered in cancer cell culture experiments.…”
Section: Discussionsupporting
confidence: 49%
“…3A). This concentration (100 µM) is approximately double that of reported cisplatin IC 50 values in some cancer cell lines [4243] and equivalent to or below IC 50 values in some cisplatin resistant cell lines, e.g., A2780/C30, MDA/CH [4244]. Therefore, our tissue culture assay found statistically significant ROS release at cisplatin concentrations encountered in cancer cell culture experiments.…”
Section: Discussionsupporting
confidence: 49%
“…Whilst DTIC chemotherapy is the standard treatment, <20% of patients respond at all to the treatment and <5% continue to respond to long-term treatment (28,29). Previous studies have demonstrated that, in the case of melanoma, resistance to DTIC is associated with low levels of apoptosis and increasing levels of anti-apoptotic proteins (19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, the cytotoxicity of cisplatin was determined by a live cell microfluorometric assay 19 . MDA/S and MDA/R cells were seeded in 6-multiwell culture plates at 10,000 cells/well.…”
Section: Live Cell Microfluorometric Assaymentioning
confidence: 99%